Implementation plan for training journals used to increase motivation and performance - Milbrath, M. J.; Humble, K. W. (Olympic & Paralympic Coach, 2015)
Just as a classroom has different curricula for its various subject matters, this implementation plan serves as one piece to the complex environment of sport and competition. This implementation plan centers on the ability of the athlete to plan, perform, and reflect in order to better focus training efforts while increasing motivation. Care should be taken to avoid overwhelming the athlete through use of a behavior contract, introducing skills gradually and deliberately, and providing peer support. Coaches can then evaluate the effectiveness of training journal use by assessing motivation and self-regulation abilities. Finally, all of these considerations should be taken under the umbrella of the athlete-centered training model using the coach`s relationship with an understanding of the athlete to direct training journal use.